Repair effect of the poly (D,L-lactic acid) nanoparticle containing tauroursodeoxycholic acid-eluting stents on endothelial injury after stent implantation - Zhou, Jiedong; Weng, Jingfan; Huang, Xingxiao; Sun, Shimin; Yang, Qi; Lin, Hui; Yang, Jinjin; Guo, Hangyuan; Chi, Jufang (Frontiers in Cardiovascular Medicine, 2022)
Background Chronic endoplasmic reticulum stress (ERS) plays a crucial role in cardiovascular diseases. Thus, it can be considered a therapeutic target for these diseases. In this study, poly(D,L-lactic acid) (PDLLA) nanoparticle-eluting stents loaded with tauroursodeoxycholic acid (TUDCA), an ER stress inhibitor, was fabricated to assess their ability to reduce endothelial cell apoptosis and promote re-endothelialization after stent implantation. Methods PDLLA nanoparticles loaded with TUDCA were prepared via the emulsification-solvent evaporation method. The cumulative release rates of TUDCA were measured in vitro via high-performance liquid chromatography. The carotid arteries of rabbits were subsequently implanted with stents in vivo. The rabbits were then sacrificed after 4 weeks for scanning electron microscopy. Meanwhile, TUDCA concentration in the homogenate of the peripheral blood and distal vascular tissue after stent implantation was measured. The effect of TUDCA on ERS, apoptosis, and human umbilical vein endothelial cell (HUVEC) function was investigated in vitro by performing cell migration assay, wound healing assay, cell proliferation assays, endoplasmic reticulum (ER)-specific fluorescence staining, immunofluorescence, and western blotting. Results TUDCA nanoparticles were released slowly over 28 days. In addition, TUDCA-eluting stents enhanced re-endothelialization and accelerated the recovery of endotheliocytes in vivo. ERS and apoptosis significantly increased in H2O2-treated HUVECs in vitro. Meanwhile, TUDCA reduced apoptosis and improved function by inhibiting ERS in H2O2-treated HUVECs. Decreased rates of apoptosis and ERS were observed after silencing XBP-1s in H2O2-treated HUVECs. Conclusions TUDCA can inhibit apoptosis and promote re-endothelialization after stent implantation by inhibiting IRE/XBP1s-related ERS. These results indicate the potential therapeutic application of TUDCA as a drug-coated stent.